2014
DOI: 10.1002/anie.201400483
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Shape Sensitivity in Palladium‐Catalyzed Suzuki–Miyaura Cross Coupling Reactions

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 57 publications
5
102
1
Order By: Relevance
“…Noble metal nanoparticles (NPs) and their alloys are of interest to wide range of areas such as electronics 1 , photovoltaics 2 , biomedical and catalysis 3 . Silver (Ag) and gold (Au) NPs are particularly important due to their unique optical properties which enables a range of applications such as surface enhanced Raman scattering (SERS) 4 , plasmonic sensors 5 , bioimaging and cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal nanoparticles (NPs) and their alloys are of interest to wide range of areas such as electronics 1 , photovoltaics 2 , biomedical and catalysis 3 . Silver (Ag) and gold (Au) NPs are particularly important due to their unique optical properties which enables a range of applications such as surface enhanced Raman scattering (SERS) 4 , plasmonic sensors 5 , bioimaging and cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The structure dependent activity trend was found to be cubic > cuboctahedra > octahedral NPs. A combination of TEM, inductively coupled plasma (ICP) and x-ray photoelectron spectroscopy (XPS), revealed that the reactivity trend originated from the facetpreferred dissolution of the (100)-enclosed cubic NPs.…”
Section: Designing Catalytic Nanoparticles To Probe Reaction Mechanismsmentioning
confidence: 94%
“…According to Gaikwad et al [56] Pd 0 atom and Pd II ion leach simultaneously and this simultaneous leaching underpins the catalysis in the SMXR. High-index surface facets have also been correlated with high catalytic activity as a result of increased Pd leaching [57,58].…”
Section: The Mechanism Of Catalysis By Nanoparticles-on the Surface Omentioning
confidence: 99%